Factors Affecting Water Consumption, An Application of Behavioral Economics: A Case Study of Yazd City - Zahra Nasrollahi; Samira Riga (اقتصاد شهری)
Economic growth, population growth, income increase, and urbanization are important factors that have increased water demand. Following the rise in demand for fresh water, the scarcity of this vital resource has become one of the main concerns of policymakers and the proper management of water resources has become one of the policy priorities. Although the use of pricing strategies is an available option in this field, the low elasticity of water demand has limited the effectiveness of this policy tool, so researchers have considered the use of non-pricing policies as a complementary strategy in the success of planning to control water scarcity in policymakers' plans to reduce demand for water resources. In this regard, the present study has investigated the effect of non-pricing strategies on water consumption. In this study, households were provided with labels containing information about each household's water consumption and its comparison with the average consumption of the neighborhood. A pair t-test for regions one and two of Yazd city during the period 1397-1397 was used to investigate the effect of non-pricing strategies on water consumption. The results showed that the mean difference in pre-test-post-test stages was significant in both regions. The average water consumption of subscribers decreased by 8.015 units in Region One and 7.041 units in Region Two.